2019
DOI: 10.1177/2050313x19828235
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the uterine cervix displaying tumor-associated tissue eosinophilia

Abstract: Background:Tumor-associated tissue eosinophilia is defined as an inflammatory response with the marked infiltration of eosinophils within tumor tissues. Tumor-associated tissue eosinophilia has been reported in various organs; however, no studies have examined the detailed cytopathological findings of tumor-associated tissue eosinophilia.Case Presentation:A 49-year-old woman presented with lower abdominal and back pain that had started 1 month earlier. A cervical biopsy revealed a diagnosis of non-keratinizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is proved that eosinophils play a pivotal role in several immunological diseases and malignancies [35]. Several previous studies observed eosinophilia in patients with both solid tumors and lymphoma [36][37][38]. On the one hand, eosinophils exert great influence in tumoricidal response.…”
Section: Discussionmentioning
confidence: 99%
“…It is proved that eosinophils play a pivotal role in several immunological diseases and malignancies [35]. Several previous studies observed eosinophilia in patients with both solid tumors and lymphoma [36][37][38]. On the one hand, eosinophils exert great influence in tumoricidal response.…”
Section: Discussionmentioning
confidence: 99%
“…It is proved that eosinophils play a pivotal role in several immunological diseases and malignancies [32]. Several previous studies observed eosinophilia in patients with both solid tumours and lymphoma [33][34][35]. On the one hand, eosinophils exert great in uence in tumoricidal response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, eosinophils work with DCs and T cells to produce inflammatory and adaptive immune responses [200]. A patient's eosinophil count can predict the immune response in cervical SCC, and high levels of eosinophils can result in poor survival (Figure 1B) [201,202]. Hypoxic conditions influence the function of EOs during cancer progression.…”
Section: Eosinophils In the CC Timementioning
confidence: 99%
“…DCs are an essential immune system component that can either enhance or suppress tumor response [200][201][202][203][204][205][206][207]. The different types of DCs, including conventional DCs (cDC1s and cDC2s), plasmacytoid DCs (pDCs), and mature DCs, express varying levels of costimulatory molecules and immune checkpoints, depending on the type and stage of the tumor [208,209].…”
Section: Dcs In the CC Timementioning
confidence: 99%